Genetic and phenetic analyses of Bradyrhizobium strains nodulating peanut (Arachis hypogaea L.) roots. - Van Rossum, D (1995)
Seventeen Bradyrhizobium sp. strains and one Azorhizobium strain were compared on the basis of five genetic and phenetic features: (i) partial sequence analyses of the 16S rRNA gene (rDNA), (ii) randomly amplified DNA polymorphisms (RAPD) using three oligonucleotide primers, (iii) total cellular protein profiles, (iv) utilization of 21 aliphatic and 22 aromatic substrates, and (v) intrinsic resistances to seven antibiotics. Partial 16S rDNA analysis revealed the presence of only two rDNA homology (i.e., identity) groups among the 17 Bradyrhizobium strains. The partial 16S rDNA sequences of Bradyrhizobium sp. strains form a tight similarity (> 95%) cluster with Rhodopseudomonas palustris, Nitrobacter species, Afipia species, and Blastobacter denitrificans but were less similar to other members of the alpha-Proteobacteria, including other members of the Rhizobiaceae family. Clustering the Bradyrhizobium sp. strains for their RAPD profiles, protein profiles, and substrate utilization data revealed more diversity than rDNA analysis. Intrinsic antibiotic resistance yielded strain-specific patterns that could not be clustered. High rDNA similarity appeared to be a prerequisite, but it did not necessarily lead to high similarity values between RAPD profiles, protein profiles, and substrate utilization. The various relationship structures, coming forth from each of the studied features, had low compatibilities, casting doubt on the usefulness of a polyphasic approach in rhizobial taxonomy.